Multicultural experiences reduce intergroup bias through epistemic unfreezing - Tadmor, Carmit T. (2013)
In 6 studies, we systematically explored for the 1st time the ameliorative effects of multicultural experience on intergroup bias and investigated the role of epistemic unfreezing as the motivational mechanism underlying these effects. We found that multicultural exposure led to a reduction in stereotype endorsement (Studies 1, 4, and 6), symbolic racism (Study 5), and discriminatory hiring decisions (Study 2). We further demonstrated that experimental exposure to multicultural experience caused a reduction in need for cognitive closure (NFCC; Studies 3 and 6) and that the ameliorative effects of multiculturalism experience on intergroup bias were fully mediated by lower levels of NFCC (Studies 4, 5, and 6). The beneficial effects of multiculturalism were found regardless of the targeted stereotype group (African Americans, Ethiopians, homosexuals, and native Israelis), regardless of whether multicultural experience was measured or manipulated, and regardless of the population sampled (Caucasian Americans or native Israelis), demonstrating the robustness of this phenomenon. Overall, these results demonstrate that multicultural experience plays a critical role in increasing social tolerance through its relationship to motivated cognitive processes.